Organizational-Economic Trends and Urgent Problems of Digitalization of the Economy of the Republic of Kazakhstan - E. Beisembai; A. A. Titkov; S. I. Zhumagalievna (Экономика: стратегия и практика)
The purpose of this scientific article is to identify modern trends in the formation of the economic and organizational foundations for the development of the digital economy of the Republic of Kazakhstan, to identify the main problems in these areas and ways to solve them. The main initial data for writing a scientific article were official statistical information in the field of development of communications and information and telecommunication technologies, scientific periodicals, including the near and far abroad, practical data of entrepreneurial structures directly leading production and economic activities in the digital and computer technology. The hypothesis of scientific research is the need to form the institutional foundations for building a digital economy, focused on the implementation of infrastructural development of digitalization processes at the macro and micro levels. The institutional framework aﬀects both the public sector and the business entrepreneurship sector. In the strategic period for the development of the digital economy, indicative programs for business structures, as well as organizational scenarios for the state, should be developed. The main methods of scientific research were analytical and synthetic, statistical, computational, and analytical research methods, the method of hypotheses. As the results of the study, attention was focused on the dynamics of the contribution of digitalization processes to the economic growth of the Republic of Kazakhstan, and the main economic problems that hinder the intensification of the development of the digital economy were identified. The main scientific contribution of the study is focused on the priorities for solving the problems of digitalization of the economy within the strategic and long-term periods, including micro- and macroeconomic levels.